Systemic sclerosis and triple-negative breast cancer: doubtful association - Singamsetty, Sushma; Thiruveedhula, Haritha; Samanthula, Haritha (Journal of Pakistan Association of Dermatologists, 2023)
Abstract: Introduction: Systemic sclerosis (Ssc) is an autoimmune connective tissue disorder, characterised by multisystem involvement, vasculopathy and fibrosis. An increased risk of breast and lung malignancy is observed in Ssc. Studies have shown 1.5 fold increase in cancer risk in Ssc. Case report: A 62 yr old female presented with hyperpigmented lesions over forehead since few months. No other significant history. On examination: Salt and pepper pigmentation over forehead, nape of the neck was seen. Tightening of skin was present over face and distal extremities with sclerodactyly. Clinically she was diagnosed as systemic sclerosis. Her routine investigations were normal except for positive ANA, and anti scl-70 antibodies. High resolution computed tomography (HRCT) chest was done to rule out asymptomatic pulmonary involvement. HRCT revealed a mass in the right breast. Lump from breast was excised and sent for histopathological examination which revealed Infiltrating duct cell carcinoma of breast. Conclusion: Thorough clinical examination and investigations must be done in every elderly female who presents with late onset systemic sclerosis for underlying breast malignancy. Likewise we have to rule out asymptomatic lung and prostate cancer in elderly men who present with late onset systemic sclerosis.